The Badlands Trail : [large type] a Ralph Compton western - Compton, Ralph; Brandt, Lyle, 1951- (Compton, Ralph. Trail drive series., 2020)
"The drovers of Circle K ranch have to drive the herd of beautiful longhorn cattle five hundred miles northeast to Missouri if they hope to make it through the next year. Toby Bishop, a jack-of-all-trades and drifter, must work with the mixed group of drovers, whether they're white, black, Hispanic, lifelong cowboys, drifters, or shamed preachers. On the trail, drovers must set aside their differences in favor of a common goal. As they go north, Bishop finds himself tested: physically by the rigors of the trail, and mentally by the grim memories evoked by the violence necessary to protect the herd. But if they are to make it all the way to St. Louis, he'll have to call on every skill and ounce of knowledge he's acquired in his checkered and violent past to overcome the unexpected obstacles threatening the drive." -- Publisher.